In vitro collateral sensitivity: a potential approach against multiple antibiotic resistant bacteria - Yousha, Nasrat Ahmed; Badhan, Sadia Islam; Dina, Shatabdi Deb; Ahsan, MD Jahid (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.